Experiences of care for self-harm in the emergency department: comparison of the perspectives of patients, carers and practitioners. Issue 5 (22nd September 2021) - O'Keeffe, Sally; Suzuki, Mimi; Ryan, Mary; Hunter, Jennifer; McCabe, Rose
Abstract : Background: Each year, 220 000 episodes of self-harm are managed by emergency departments in England, providing support to people at risk of suicide. Aims: To explore treatment of self-harm in emergency departments, comparing perspectives of patients, carers and practitioners. Method: Focus groups and semi-structured interviews with 79 people explored experiences of receiving/delivering care. Participants were patients (7 young people, 12 adults), 8 carers, 15 generalist emergency department practitioners and 37 liaison psychiatry practitioners. Data were analysed using framework analysis. Results: We identified four themes. One was common across stakeholder groups: (a) the wider system is failing people who self-harm: they often only access crisis support as they are frequently excluded from services, leading to unhelpful cycles of attending the emergency department. Carers felt over-relied upon and ill-equipped to keep the person safe. Three themes reflected different perspectives across stakeholders: (b) practitioners feel powerless and become hardened towards patients, with patients feeling judged for seeking help which exacerbates their distress; (c) patients need a human connection to offer hope when life feels hopeless, yet practitioners underestimate the therapeutic potential of interactions; and (d) practitioners are fearful of blame if someone takes their life: formulaic question-and-answer risk assessments help make staff feel safer but patients feel this is not a valid way of assessing risk or addressing their needs. Conclusions: Emergency department practitioners should seek to build a human connection and validate patients' distress, which offers hope when life feels hopeless. Patients consider this a therapeutic intervention in its own right. Investment in self-harm treatment is indicated.